GAME ONLINE BERHUBUNGAN DENGAN PERILAKU AGRESIVITAS PADA REMAJA: SEBUAH STUDI DI GAME CENTER SEMARANG - Anggreyani, Rainatha; Khasanah, Nopi Nur; Susanto, Herry (Jurnal Ilmu Kesehatan Immanuel, 2020)
Background: Teens of online game users from year to year have increased. The impact of online games on children are depression, anxiety, and social phobia will get worse and academic achievement will decrease. In addition, the addiction to online games can lead to the emergence of aggressive behavior in adolescents. Researcher is interested to examine the correlation between online game addiction with aggressiveness behavior in adolescents in Semarang game center. Methode: The design of this study is quantitative and type of  the research used Cross sectional study. The data were collected by using questionnaires. The number of respondents is 40 people used total sampling technique. The data obtained is processed statistically by using somers'd test. Result: Based on the results obtained from 40 respondents, with the characteristics of respondents 30% aged 18 years. The results showed that 52.5% showed addiction to heavy online games, 32.5% showed a moderate online game addiction and 15% showed an addiction to light online games. A total of 17.5% showed severe aggressiveness, 77.5% showed moderate aggressiveness and 5% showed mild aggressiveness. Conclusion: There is a significant correlation between online game addiction and aggressive behavior in adolescents in Semarang game center (p = 0.042), with weak correlation (r = 0.290)